Perancangan Sistem Informasi Penjualan Mesin Foto Copy Berbasis Web - Rosidin Rosidin; Baginda Oloan Lubis (LPPM STMIK ANTAR BANGSA, 2017)
Abstract-The Design of Selling Information System of Web Based Photocopy Machine. Photocopiers are a technological tool that serves to make copies onto paper from documents, books, or other sources. But buyers are still difficult to find copier machines that are very affordable, quality of the machine is very satisfactory, and do not know the reference engine suitable for their needs. Information technology has evolved and drove quickly. That enables everyone to easily access the information needed in a short time. The purpose of this final project is to make the design of selling information system of web based photocopy machine, which is a means of marketing and selling products through the Internet. The method used is by studying the literature on the working system of e-commerce websites, and then to design system work is implemented with the establishment of the e-commerce websites. Over-subscription of this website is the buyer can save time and cost in compare to come directly to the store that still sells conventional photocopy machine, and buyers can also view the product catalogue directly photocopy machine and prices contained in this web page.Â Intisari-Mesin fotokopi merupakan sebuah alat teknologi yang berfungsi untuk membuat salinan keatas kertas dokumen buku, maupun sumber lain. Tetapi pembeli masih sulit untuk menemukan mesin fotokopi yang harganya sangat terjangkau, kualitas mesin yang sangat memuaskan, serta tidak mengetahui referensi mesin yang cocok digunakan untuk kebutuhan mereka. Perkembangan teknologi internet dapat mendukung adopsi cepat sistem e-commerce. Sistem informasi penjualan mesin fotokopi berbasis web, yang merupakan sarana pemasaran dan penjualan produk melalui internet. Metode yang digunakan adalah dengan mempelajari literatur tentang sistem kerja website e-commerce, dan kemudian merancang kerja sistem yang diimplementasikan dengan berdirinya situs web e-commerce. Kelebihan dari situs ini adalah pembeli dapat menghemat waktu dan biaya jika dibandingkan langsung datang ke toko yang masih menjual mesin fotokopi konvensional, dan pembeli juga bisa melihat katalog produk mesin fotokopi secara langsung dan harga yang terdapat di halaman web ini.Kata Kunciâ€” Perancangan sistem Informasi, sistem penjualan mesin fotokopi, web